PELAKSANAAN PROGRAM PENINGKATAN PRODUKTIVITAS TENAGA KERJA PADA USAHAMIKRO KECIL DAN MENENGAH OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI RIAU DI KOTA PEKANBARU PADA TAHUN 2018 - Thasa Nadilla; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Increasing Labor Productivity in Micro, Small and Medium Enterprises, various MSME businesses is a program carried out by the Department of Manpower and Transmigration which consists of various types of businesses, such as culinary businesses, to manufacturing. However, in line with the development of the government's economic policy, MSMEs are currently faced with free competition from national to international scale companies. With the hope of being able to improve the economy in Pekanbaru CityThe purpose of this research is to find out the implementation of the Program for Increasing Labor Productivity in Micro, Small and Medium Enterprises in Pekanbaru City in 2018 and want to know the inhibiting factors in the implementation of this program. This study uses a qualitative approach with a descriptive method. `In collecting data, the author uses interview techniques, mass media, and documentation.The results of this study found that there are three elements called the conformity model, namely the program, program implementers, and program targets. In the first element, the alignment of the Workforce Productivity Improvement Program in Pekanbaru City with the needs of the program target, namely business actors where this program is designed and adapted to the acceleration of the regional economy. In the second element, the Program Implementer, namely the management of the implementation of the alignment of the Workforce Productivity Improvement Program in this case is not optimal, the program implementer is still lacking in related instructors. In the third element, in this case the business actors themselves as the target of the program, there are still many who do not have complete data and business permits as the main requirements for program recipients. There are still inhibiting factors in this program, both external and internal, making the implementation of the program to increase labor productivity in Pekanbaru City cannot be realized optimally.  Keywords: Increasing Labor Productivity, Programs, Program Implementation, Program Targets.